Women's mobilisation in the Portuguese revolution: context and framing strategies. (3rd July 2016) - Melo, Daniela F.
Abstract: This article examines the role of women's mobilisations related to the 1974 Portuguese revolution. An in-depth analysis of three women's organisations through archival research and interviews with participants highlights the ways in which they participated in a cycle of contention between 1974 and 1977. Examination of framing strategies demonstrates the effects of political and cultural context. In particular, I demonstrate that movement–party alliances informed and constrained the diagnostic and prognostic frames of women's movements on feminism and the revolution. Opportunity structures are shown to vary for different organisations within the same cycle of contention. Facing relatively closed opportunities, two of these organisations pursued framing strategies that articulated with the Left-dominated master frame of the cycle in order to carve out spaces for gender-specific demands while rejecting the label of feminism. The third organisation, instead, presented a countercultural frame that alienated the organisation from party and movement allies. Unable to overcome ideological divisions and rivalries, the three organisations perceived each other as competitors, rather than potential allies. While party–movement cooperation contributed to the emergence of a fractionalised women's movement, it also provided important support structures to aid women's organisations to mobilise in a cultural and political context that was closed to feminist demands.